An Accident of Geography? Assessing the Gerrymandering of School Attendance Zones. Issue 7 (July 2015) - Richards, Meredith P.; Stroub, Kori J.
Context: Despite the recent emphasis on public school choice, more than four-fifths of public school students still attend the traditional school to which they are assigned (NCES CCD, 2013), making attendance zone boundaries critical and fercely contested determinants of educational opportunity. Historical and anecdotal evidence suggests that attendance zone boundaries are not "accidents of geography, " but have been "gerrymandered" into irregular shapes in ways that alter patterns of student attendance. However, no empirical evidence has directly examined the issue of attendance zone gerrymandering. Purpose of Study: Drawing on the literature on electoral gerrymandering, we outline a framework for conceptualizing and measuring educational gerrymandering. Using geospatial techniques, we then provide initial empirical evidence on the gerrymandering of school attendance zones and the variation in gerrymandering across geographic and demographic contexts. Research Design: We analyze the boundaries of a large national sample of 23, 945 school attendance zones obtained from the School Attendance Boundary Information System (SABINS). For each attendance zone, we compute complementary measures assessing two dimensions of gerrymandering: (1) dispersion, or the elongation of the area of a boundary; and (2) indentation, or the irregularity of the perimeter of a boundary. Results: Overall, we find that attendance zones are highly gerrymandered—nearly as much as legislative districts—and are becoming more gerrymandered over time. Findings underscore the racial and, to a lesser extent, socioeconomic character of gerrymandering, which is particularly acute in Whiter and more affluent schools and in areas experiencing rapid racial change. Conclusions: The gerrymandering of school attendance zones has significant implications for students and schools. Gerrymandering alters patterns of attendance and, thereby, student access to educational opportunity and resources, by "zoning out" certain students living closer to schools while "zoning in" others living farther away. Gerrymandered boundaries also hold the potential to significantly alter the racial and ethnic composition of schools and may serve as a mechanism of segregation. In addition, gerrymandered attendance zones are inherently inefficient and may impose additional transportation costs on students and districts. We conclude with implications for state and federal policy.